2021
DOI: 10.3390/toxins13120892
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Involvement of a Cyclase Gene in the Biosynthesis of Ochratoxin A in Aspergillus carbonarius

Abstract: Ochratoxin A (OTA) is a well-known mycotoxin with wide distribution in food and feed. Fungal genome sequencing has great utility for identifying secondary metabolites gene clusters for known and novel compounds. A comparative analysis of the OTA-biosynthetic cluster in A. steynii, A. westerdijkiae, A. niger, A. carbonarius, and P. nordicum has revealed a high synteny in OTA cluster organization in five structural genes (otaA, otaB, ota, otaR1, and otaD). Moreover, a recent detailed comparative genome analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The presence of these fungi on pomegranate is relevant from a sanitary point of view, since A. welwitschiae strains are potential producers of the mycotoxins fumonisins and ochratoxins [ 19 , 76 ]. Tested isolates proved to be positive for the presence of genes fum8 and fum15 of the fumonisin pathway, but negative for genes involved in OTA biosynthesis [ 26 ], although Ferrara et al [ 77 , 78 ] confirmed the presence of this biosynthetic pathway in A. welwitschiae . Some of the strains were tested by HPLC [ 26 ] to evaluate the amount of these mycotoxins, showing concentrations of FB over the admitted threshold (CE 1126/07) for other plant products.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these fungi on pomegranate is relevant from a sanitary point of view, since A. welwitschiae strains are potential producers of the mycotoxins fumonisins and ochratoxins [ 19 , 76 ]. Tested isolates proved to be positive for the presence of genes fum8 and fum15 of the fumonisin pathway, but negative for genes involved in OTA biosynthesis [ 26 ], although Ferrara et al [ 77 , 78 ] confirmed the presence of this biosynthetic pathway in A. welwitschiae . Some of the strains were tested by HPLC [ 26 ] to evaluate the amount of these mycotoxins, showing concentrations of FB over the admitted threshold (CE 1126/07) for other plant products.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the identified protein kinases were found to be necessary for both hyphal septation and A. fumigatus ’s capacity to invade lung tissue. In addition to these industrially important strains and pathogenic strains, this versatile genetic manipulation tool has also been successfully established and applied to other Aspergillus species, including A. carbonarius , A. novofumigatus , and A. terreus , among others [ 99 , 100 , 101 , 102 ]. More studies on the development and utilization of the CRISPR/Cas9 genome editing technology in Aspergillus are summarized in Table 1 .…”
Section: Development and Application Of Crispr/cas9-based Genome Edit...mentioning
confidence: 99%
“…Recently, a cyclase gene otaY was proved to be involved in the biosynthesis of ( 1 ) ( Figure 2 ). OtaY was speculated to catalyze the cyclization process of 7-methylmellein ( Ferrara et al, 2020 ; Ferrara et al, 2021 ).…”
Section: Secondary Metabolites From a Ochraceusmentioning
confidence: 99%